Locating South Africa within the global adventure tourism industry: the case of bungee jumping - McKay Tracey M. (Bulletin of Geography. Socio-Economic Series, 2014)
Bungee jumping is a global phenomenon and is an important sector of the adventure tourism market, acknowledged as an iconic form of hard adventure. Commercial operators are located in North and South America, Asia, Europe and Australasia. In Africa, commercial bungee jumping takes place in Uganda, Zambia and South Africa. This paper fills a gap in the international literature by firstly providing an overview of the global bungee industry, and secondly locating the South African bungee jumping sector within it. Thus, the supply side of the market is analysed geographically, with a focus on iconic, African and South African jump sites. The study found that bungee jumping takes on a similar form across the globe, notably, a high staff to client ratio; the need for strict safety measures; the provision of additional adventure activities on or near the site and the sale of souvenirs. The paper presents the hither to unknown commercial signature of bungee jumping. Finally, the case for South Africa’s commercial bungee jumping industry as a globally being globally competitive one is presented.